2023
DOI: 10.3390/jcm12031137
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Human Amniotic Membrane Patching Assisted Vitrectomy in the Management of Postoperative PVR in Complex Retinal Detachments

Abstract: Human amniotic membranes (hAMs) are extraembryonic tissues currently employed in the treatment of many ocular and systemic diseases. Several reports indicate that hAMs can suppress the signaling pathway of tissue growth factor beta (TGF-β), a cytokine that plays a major role in the pathogenesis of proliferative vitreoretinopathy (PVR) through the induction of epithelial-mesenchymal transition (EMT) in exposed retinal pigmented epithelium (RPE) cells. The present study was conducted to evaluate the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Recently, Caporossi et al [ 142 ] evaluated the efficacy of a modified vitrectomy procedure involving the coverage of exposed RPE in retinal breaks and retinotomy with human amniotic membrane (hAM) patches to prevent postoperative PVR in a series of 15 cases of retinal detachment complicated by severe preoperatory PVR, assuming that hAM can suppress the TGF-β pathway in a selected population of cells involved in the pathogenesis of PVR, including fibroblasts, macrophages, and particularly RPE cells.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Recently, Caporossi et al [ 142 ] evaluated the efficacy of a modified vitrectomy procedure involving the coverage of exposed RPE in retinal breaks and retinotomy with human amniotic membrane (hAM) patches to prevent postoperative PVR in a series of 15 cases of retinal detachment complicated by severe preoperatory PVR, assuming that hAM can suppress the TGF-β pathway in a selected population of cells involved in the pathogenesis of PVR, including fibroblasts, macrophages, and particularly RPE cells.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…However, compared to atrophic retinal diseases, PVR is caused by a severe fbrotic cell response to retinal detachment [11,12]. Despite the diferent pathogenesis, frst intraocular implantations of AM in case series with complex retinal detachments at high risk for PVR development also indicated a benefcial efect [13,14]. Other studies showed that AM may promote wound healing through fbroblast proliferation and induction of migration and expression of the extracellular matrix [15].…”
Section: Introductionmentioning
confidence: 99%